15 Not all the Hype is about Hypos: Local Experience of a Multidisciplinary Diabetes Consultation Service for Older Persons. (16th September 2019) - Costello, Maria; Newman, Christine; Dennehy, Karen; Reddin, Caitriona; Abdullah, Abdullah; Cunningham, Aine; Reddington, Lisa; Burke, Helen; Bell, Marcia; Dinneen, Sean; O' Sullivan, Esther
Abstract: Background: Diabetes is a prominent health problem with prevalence increasing as the population ages. It is estimated that 11.9% of the Irish population aged 75 years and older are living with type 2 diabetes. This condition puts older people at risk of polypharmacy, incontinence in setting of poor control and neuropathic pain. In addition, they are at risk of premature death and functional impairment arising from associated complications. There is an estimated resource use of 10% of the total healthcare budget including medication costs, hospitalisations and attending non-diabetic specialists for disease associated complications. Methods: We reviewed all acute hospital diabetes consultations over a two-month period to identify persons aged 75 years and over who had contact with our clinical nurse specialists and consult service. Results: 46 patients aged 75 years and older (median age 79 years) were reviewed on request by the consults service. 6.5% (n=3) had Type 1 Diabetes. 41.3% (n=19) were on insulin and the remainder were on oral medications alone. They had a median HbA1c of 63mmol/mol. 91.3% (n=42) were living at home prior to admission. All patients were reviewed and educated by our clinical nurse specialists. Issues addressed included hypoglycaemic awareness, glucometer use and insulin administration. 17.4% (n=8) had medications discontinued due to hypoglycaemia and/or chronic kidney disease. 32.6% (n=15) had up-titration of insulin and/or addition of new agents. 58.7% (n=27) were subsequently followed up in clinic by telephone. Conclusion: The 2018 American Diabetes Association guidelines now recommend treatment goals based on functional status rather than age. Our experience locally is reflective of the spectrum of issues that arise in management of diabetes in the older person. This highlights the positive impact of a multidisciplinary diabetes service in minimising complications and promoting individualised person-centred care.